Change One Thing : Discover What's Holding You Back and Fix it With the Secrets of a Top Executive Image Consultant - Wildermuth, Anna Soo and Gould, Jodie (New York Mc,Graw-Hill, 2009)
An acclaimed image consultant and coach shows how making small changes, one at a time, can polish your presentation and transform your career and personal life.
Includes Index.
Keywords: Self-help Techniques -- Success in Business -- Interpersonal Communication